Exploring identity: a figurative character image-elicitation approach. Issue 2 (3rd June 2014) - Butler, Clare; Finniear, Jocelyn; Marie Doherty, Anne; Hill, Steve
Abstract : Purpose: – The purpose of this paper is to explore the potential of incorporating visual methods in the study of identity and identity work. Design/methodology/approach: – Scholars have proposed a range of approaches to the study of identity. However, studies have typically relied on interviews or surveys with little exploration of the dynamic narrating of self- in-situ inherent to identity and identity work. The paper reviews the aforementioned methods, builds on the power of visual approaches, and proposes a method involving figurative character image-elicitation (FCI). FCI uses personal, contextual cartoon-style images to mobilize and encourage the narration of identity. The paper details the development of the approach, drawing on a pilot study, and reports its use in an exploratory study of employee identity. Findings: – The results suggest that the use of FCI provides a situated focus for the narration of identity with the signifying – self- insitu – nature of the images providing room for participants to position themselves as subject. These features are also suggested to provide a safe distance for a more in-depth and expressive discussion which transcends impression management. Originality/value: – The use of FCI has highlighted the power of visual methods in the exploration of identity and identity work. The approach is personally engaging and contextually adaptable providing methodological opportunities for a range of organizational and societal studies.